Information-theoretic cryptography - Tyagi, Himanshu; Watanabe, Shun. (2023)
"This book offers a mathematical foundation for modern cryptography. It is primarily intended as an introduction for graduate students. Readers should have a basic knowledge of probability theory, but familiarity with computational complexity is not required. Starting from Shannon's classic result on secret key cryptography, fundamental topics of cryptography, such as the secret key agreement, authentication, secret sharing, and secure computation, are covered. Particular attention is drawn to how correlated randomness can be used to construct cryptographic primitives"--
Includes bibliographical references and index.
Keywords: Cryptography; Cryptography -- Mathematics